Analisis Framing Berita Pemberhentian Sementara Bupati Aceh Selatan di Media Online Detik.Com dan CNN Indonesia.Com - Septika, Ghina; Azhar, Anang Anas (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The development of online media has strengthened the role of mass media in shaping the construction of social reality through the presentation of information in news texts. Media coverage is not always neutral, as each media outlet tends to highlight certain aspects of an event through the framing process. This study aims to analyze how the online media Detik.com and CNNIndonesia.com frame the news regarding the temporary suspension of the Regent of South Aceh. This research employs a qualitative approach with a descriptive method. The research data consist of news texts related to the temporary suspension of the Regent of South Aceh published during the period of December 8–10, 2025. Data were collected through documentation by tracing and gathering news articles from the two online media platforms. Data analysis uses the framing analysis model developed by Zhongdang Pan and Gerald M. Kosicki, which includes syntactic, script, thematic, and rhetorical structures to identify how the media organize facts, select sources, emphasize certain issues, and construct narratives in their news coverage. The results show that Detik.com and CNNIndonesia.com frame the event of the temporary suspension of the Regent of South Aceh differently, particularly in terms of information emphasis, source selection, and narrative construction presented to the public.